2021
DOI: 10.1177/14613557211027189
|View full text |Cite
|
Sign up to set email alerts
|

Does motivational regulation affect physical activity patterns among Norwegian Police University College students?

Abstract: Physical readiness is important for operative police officers to cope with occupational tasks. Despite this, physical activity and physical fitness among police officers decrease throughout their occupational career. Self-determination theory (SDT) is a major theoretical approach in motivation research for sports and physical activity. SDT describes types of motivation and motivational regulation and how they are related to physical activity and physical activity adherence. This study aims to explore whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It should be noted that although dietary interventions can be beneficial for improving factors that relate to CVD risk (e.g., blood lipid profiles, weight management) [39,86,87], these interventions should be made within the context of occupational challenges and motivations experienced by police officers [13]. This is also true for physical activity [8,88]. Indeed, the potential benefit of health and wellness programs designed for police departments is that they can cater to specific needs and constraints of officers.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that although dietary interventions can be beneficial for improving factors that relate to CVD risk (e.g., blood lipid profiles, weight management) [39,86,87], these interventions should be made within the context of occupational challenges and motivations experienced by police officers [13]. This is also true for physical activity [8,88]. Indeed, the potential benefit of health and wellness programs designed for police departments is that they can cater to specific needs and constraints of officers.…”
Section: Discussionmentioning
confidence: 99%
“…Although this population is perceived as healthy, <27% of students described their lifestyle to be active (Yahia et al, 2016), and reduced PA levels were observed among this population due to the Covid-19 pandemic (Gallo et al, 2020). Previous studies showed that SDT improved PA rates among students (Jenssen and Dillern, 2021) likewise ACT (Wang et al, 2020). Specifically, young adults may gain mental and physical advantages by assimilating the protocol of the SDT and ACT-based intervention group and facilitates PA adherence throughout their professional career.…”
Section: Limitations Future Directions and Implicationsmentioning
confidence: 93%
“…The literature review revealed that physical activity patterns in policing work time [11], motivational regulation of police college students [12], physical activity levels in police o cers and cadets [13], and if self-e cacy for exercise predictive of leisure-time physical activity [14]. Previous studies about physical exercise mainly focused on teenagers or ordinary adult population, and the results of these researches contained nding out their motivation, exercise programs and in uencing factors [15,16].…”
Section: Introductionmentioning
confidence: 99%